GREG HEFFLEY’S ROLE CONFUSION IN THE DIARY OF A WIMPY KID (2007): A PSYCHOSOCIAL ANALYSIS - Heri Dwi Santoso; Dwi Ario Fajar (Lire Journal (Journal of Linguistics and Literature), 2023)
Literary psychological scholars see psychological problems faced by a fictional character in a literary work as a reflection of the author’s awareness of similar phenomena that happen to a real person in real life. It becomes a trigger to why this research is conducted. This research aims to analyze the psychological condition of Greg Heffley, the protagonist in the Diary of a Wimpy Kid (2007), in his early teenage year. The theory used in this research is Erik Erikson’s theory of psychosocial development. This research method is qualitative descriptive, where data is analyzed and presented in the discussion in detailed descriptions. Meanwhile, the primary data is text in the novel. The results show that Greg Heffley, as the protagonist, experiences role confusion due to the transition from childhood to teenage. He does not adapt well with his new environment. The situation is worsened by his unsupportive best friend, who still acts like a child when interacting with him. It is also found that Greg Heffley, at this stage, begins to be aware of his sexual and occupational identity. It is concluded that Greg Heffley finds it challenging and difficult to migrate from childhood to teenage with all his situation.